Ruxolitinib Has a Protective Effect on Ovarian and Endometrial Tissues in Diabetic Rats via STAT3 Pathway - Savaş Özdemir; Fatih Şahin; Oytun Erbaş (Clinical and Experimental Obstetrics & Gynecology)
Background: Hyperglycemia is associated with ovarian dysfunction. Advanced glycation end products (AGE) may affect ovarian function by binding to particular AGE receptors (RAGE). Hematopoiesis and immunological conditioning are both controlled by the Janus kinase/signal transducer and activator of transcription (JAK/STAT) signaling pathway. Many JAK-STAT signaling inhibitors, including ruxolitinib, have been approved to treat inflammatory disorders. We aimed to examine the potential protective effect of ruxolitinib, on ovarian dysfunction by comparing biochemical, pro-inflammatory, and histological abnormalities in a diabetic rat model. Methods: 24 female Wistar albino rats were included in the study. Diabetes was induced by streptozotocin (STZ) in 16 rats. Group 1: control (no diabetes mellitus, n = 8), Group 2 (diabetic = 8, 1 mL/kg/day saline, 4 weeks), and Group 3 (diabetic, n = 8, 2 mg/kg/day ruxolitinib, 4 weeks). The animals were euthanized, and bilateral hysterectomy and ovariectomy were performed for histopathological examination. The levels of signal transducer and activator of transcription 3 (STAT3) in tissue supernatants were measured. Results: Endometrial gland, ovarian stromal, and ovarian follicle degeneration scores were higher in group 2 compared with group 3 at p < 0.001, whereas ovarian STAT3 level was significantly higher in group 2 compared with group 3 at p < 0.001. Conclusions: Ruxolitinib can be a promising candidate for providing endometrial and ovarian structure continuity by JAK-STAT inhibition in diabetes.